2001
DOI: 10.1073/pnas.141041098
|View full text |Cite
|
Sign up to set email alerts
|

Binding and disruption of phospholipid bilayers by supramolecular RNA complexes

Abstract: In an RNA world, RNAs would have regulated traffic through normally impermeable bilayer membranes. Using selection-amplification we previously found RNAs that bind stably and increase the ionic conductance of phospholipid membranes at high Mg 2؉ and Ca 2؉ concentrations. Now selection in reduced divalents yields RNAs that bind phosphatidylcholine liposomes under conditions closer to physiological. Such affinity for phospholipid membranes requires interactions between RNAs. In fact, we detected no functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
121
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(131 citation statements)
references
References 17 publications
(17 reference statements)
8
121
2
Order By: Relevance
“…Following such an evolutionary rationale, RNAs that can bind, change the permeability, and disrupt phospholipid bilayers have been isolated using selection-amplification (Khvorova et al 1999;Vlassov et al 2001). The oligomerizing heterotrimer RNA (9:9:10) n ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following such an evolutionary rationale, RNAs that can bind, change the permeability, and disrupt phospholipid bilayers have been isolated using selection-amplification (Khvorova et al 1999;Vlassov et al 2001). The oligomerizing heterotrimer RNA (9:9:10) n ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The oligomerizing heterotrimer RNA (9:9:10) n ( Fig. 1; Vlassov et al 2001) was one particular example, found to bind stably to the exposed face of a phosphatidylcholine vesicle. Because many RNA complexes with similar activities were isolated, with no sequences in common, many RNA structures exist that bind phospholipid membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of RNA aptamers was performed in low ionic-strength buffer (with a low concentration of monovalents, and a physiological concentration of divalents) against DOPC molecules forming 100-nm liposomes [53]. During the selection, the liposome-bound RNAs were separated from the unbound ones using gel chromatography.…”
Section: Aptamers That Bind Dopc Liposomesmentioning
confidence: 99%
“…At first, the requirements imposed on early membranes by the lack of protein transport assemblies, and of stabilizing structures, such as cytosomal support proteins or cell walls suggests relatively permeable membrane boundaries which are best modeled by fattyacid vesicles (see Table 1). As the early cells began to synthesize polymeric molecules (perhaps RNA fragments (Khvorova et al, 1999;Vlassov et al, 2001), small polypeptides (Ghadiri et al, 1994;Oliver and Deamer, 1994;Clark et al, 1998;Kim et al, 1998), or other molecules that could mediate simple transport processes), more robust mixed amphiphile membranes that are modeled by short-chain phospholipid/fatty acids mixtures (such as DMPC/MA) would have replaced them. Finally, as populations of microbial organisms increasingly were able to produce their own specific amphiphiles, membranes of more homogenous composition would have appeared.…”
Section: Prebiotic Plausibility Of Various Membrane Modelsmentioning
confidence: 99%